A systematic review of research on abusive supervision in hospitality and tourism. Issue 7 (12th June 2020) - Yu, Yitong; Xu, Shi; Li, Gang; Kong, Haiyan
Abstract : Purpose: This paper aims to provide researchers and practitioners with an understanding of abusive supervision in the context of hospitality. It seeks to conduct a comprehensive review of the area and offer recommendations for future research by exploring the antecedents, consequences, mechanisms and designs of research on abusive supervision. Design/methodology/approach: Content analysis was conducted to review and analyze studies on abusive supervision in the context of hospitality. Previous studies were searched in the EBSCO, Scopus, Web of Science and Google Scholar electronic databases. Findings: In total, 36 referred articles related to abusive supervision in hospitality were reviewed across four key areas, namely, antecedents, consequences, mechanisms and research design. After reviewing the research on abusive supervision in the context of hospitality, this paper offers future research directions with respect to research focus and research design. Research limitations/implications: This paper only included English articles from peer-reviewed journals on abusive supervision. The number of reviewed articles was relatively small. This limitation may have arisen because abusive supervision is a new research field and is still a sensitive topic. Practical implications: The results of this study may encourage managers to minimize or even halt abusive supervision. From an organizational perspective, formal policies may be developed to regularize supervisors' behavior. In turn, employees could use this paper to learn further about abusive behavior and how to handle it effectively. Social implications: The review highlighted the negative consequences of abusive supervision. Managers should urgently realize the seriousness of abusive supervision and develop effective policies to minimize its negative effect. Originality/value: This paper contributes to the emerging literature on abusive supervision in the context of hospitality by identifying key research trends and framing the outlines of empirical studies. It identifies research gaps, and as the first review of abusive supervision in hospitality, it may encourage researchers to explore the topic on the basis of the characteristics of the sector and offer suggestions for future research.